2017
DOI: 10.1097/icb.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Epiretinal Membrane Formation After Intravitreal Autologous Stem Cell Implantation in a Retinitis Pigmentosa Patient

Abstract: This is the first report of ERM formation following intravitreal autologous stem cells injection. CD34-positive stem cells were detected in a human eye at 4 months after injection. Further studies are needed to determine how stem cells caused ERM and how long they would stay in the eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…Detailed reports of the results of these trials are pending, but several serious adverse effects associated with BMSC therapy from unregulated clinical studies have been reported recently. They include retinal detachment, severe macular pucker, and retinal artery occlusion following subretinal, intravitreal and periocular injections of BMSCs (Boudreault et al, 2016; Kim et al, 2016; Leung et al, 2016). Some of these adverse effects mirror reactive retinal gliosis, fibrovascular proliferation and vascular obstruction observed in preclinical studies using intravitreal and intravascular mesenchymal stem cells (Ge et al 2014; Tassoni et al, 2015; Figure 3).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Detailed reports of the results of these trials are pending, but several serious adverse effects associated with BMSC therapy from unregulated clinical studies have been reported recently. They include retinal detachment, severe macular pucker, and retinal artery occlusion following subretinal, intravitreal and periocular injections of BMSCs (Boudreault et al, 2016; Kim et al, 2016; Leung et al, 2016). Some of these adverse effects mirror reactive retinal gliosis, fibrovascular proliferation and vascular obstruction observed in preclinical studies using intravitreal and intravascular mesenchymal stem cells (Ge et al 2014; Tassoni et al, 2015; Figure 3).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…These complications are sometimes associated with the surgery. However, more studies showed that intravitreal transplantation of other kinds of stem cells also resulted in ERM formation [18][19][20], which suggest that not only surgery process but also transplantation sites may affect therapeutic outcomes. When stem cells are used to treat RDD, cells can be transplanted into the subretinal space or the vitreous chamber.…”
Section: Introductionmentioning
confidence: 99%
“…ERM attaches to the retina and contracts and distorts the retina [26]. Previous studies have shown that ERM formed in patients received intravitreal transplantation of bone marrow-derived stem cells and ASCs [17,19]. However, the ERM formation process, ERM cellular components, and the contribution of stem cells to ERM formation in these patients are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…36 There have been similar recent reports of proinflammatory vitreous clumping 37 of MSCs injected intravitreally as well as thick epiretinal membrane formation following MSC administration in humans. 38 These adverse effects may also be due in part to the inconsistency in MSC isolation and preparation. An attempt to standardise the identification of these cells led to the development of the International Society for Cellular Therapy criteria, 39 but problems continue to be reported despite this and may limit the degree to which MSCs can successfully be used to confer neuroprotection to retinal ganglion cells.…”
Section: Cell Therapymentioning
confidence: 99%